2023
DOI: 10.1186/s40168-023-01650-7
|View full text |Cite
|
Sign up to set email alerts
|

Stable functional structure despite high taxonomic variability across fungal communities in soils of old-growth montane forests

Qingchao Zeng,
Annie Lebreton,
Lucas Auer
et al.

Abstract: Background Major advances over the past decade in molecular ecology are providing access to soil fungal diversity in forest ecosystems worldwide, but the diverse functions and metabolic capabilities of this microbial community remain largely elusive. We conducted a field survey in montane old-growth broadleaved and conifer forests, to investigate the relationship between soil fungal diversity and functional genetic traits. To assess the extent to which variation in community composition was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…The growing availability of mycorrhizal fungal genomes (Lebreton et al, 2021) presents unprecedented opportunities to investigate the functional diversity of soil fungal communities. This can be achieved through expert and accurate annotation of environmental metabarcoding (Anthony et al, 2022), metagenomics (Hagh-Doust et al, 2023, and metatranscriptomic (Auer et al, 2023;Zeng et al, 2023) datasets. The latter approach has been used to examine gene expression in ECM root tips in natural environments, including the effects of anthropogenic N deposition on ECM tree metabolism (Liao et al, 2018;Law et al, 2022;Rivera P erez et al, 2022).…”
Section: Linking Genes To Ecological Traitsmentioning
confidence: 99%
See 2 more Smart Citations
“…The growing availability of mycorrhizal fungal genomes (Lebreton et al, 2021) presents unprecedented opportunities to investigate the functional diversity of soil fungal communities. This can be achieved through expert and accurate annotation of environmental metabarcoding (Anthony et al, 2022), metagenomics (Hagh-Doust et al, 2023, and metatranscriptomic (Auer et al, 2023;Zeng et al, 2023) datasets. The latter approach has been used to examine gene expression in ECM root tips in natural environments, including the effects of anthropogenic N deposition on ECM tree metabolism (Liao et al, 2018;Law et al, 2022;Rivera P erez et al, 2022).…”
Section: Linking Genes To Ecological Traitsmentioning
confidence: 99%
“…Anthony et al (2022) showed that tree growth was linked to the gene copy number of genes involved N uptake and assimilation in associated ECM symbionts. By combining highthroughput metabarcoding of fungal species residing in a specific experimental forest site with the sequencing of soil eukaryotic RNA extracts, the precise gene expression of each mycelial network extending beneath a tree species can be evaluated (Auer et al, 2023;Zeng et al, 2023). The use of metatranscriptomics will also help decipher the relative importance of each fungal species within the different soil biota in measuring genes involved in plant nutrition, C cycling, disease resistance, and stress adaptation.…”
Section: Linking Genes To Ecological Traitsmentioning
confidence: 99%
See 1 more Smart Citation